(In)vulnerable domains in multilingualism - Müller, Natascha (Hamburg studies on multilingualism, 2003)
This study has been conducted within the larger context of the project SKOBI and its research questions concerning the acquisition and development of linguistic connectivity in Turkish and German in bilingual children. The phenomenon analyzed is approached from the perspective of language typology, sociolinguistics, language psychology and acquisition theory. The paper is intended as a mainly qualitative study on one phenomenon in the language use of five Turkish-German bilingual children displaying innovative constructions of a kind not to be found in the data of the monolingual control group.